Sinergi Lintas Universitas dalam Membangun Kesadaran Pentingnya Pendidikan Bagi Generasi Muda - Ucik Ernawati; Latif Sofiana Nugraheni; Tutik Fitri Wijayanti; Purwo Adi Nugroho; Irma Yuniar Wardhani; Riza Desy Nila Ayunika; Naylil Mawadda Rohma; Dyah Erlina Sulistyaningrum (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2026)
Education plays a fundamental role in shaping the quality of human resources and determining national progress. However, many young people still lack awareness and motivation regarding the importance of education due to limited access to information, socioeconomic challenges, and insufficient understanding of its long-term benefits. This Community Service Program aims to increase young people’s awareness of the importance of education through collaboration among multiple universities. The program involved lecturers and students from various higher education institutions who conducted educational outreach activities, motivational seminars, interactive discussions, and mentoring sessions. Methods used included educational counseling, inspirational presentations, question-and-answer sessions, and participant evaluations. The results show an improvement in participants’ understanding, motivation, and awareness of education as an investment in the future. In addition, inter-university collaboration expanded the program’s reach, enriched perspectives shared with participants, and strengthened higher education institutions’ commitment to community engagement. This initiative demonstrates that cross-university synergy can serve as an effective and sustainable model for fostering educational awareness and supporting the development of future generations in diverse communities.